Penanaman Sikap Inklusif Keberagamaan Hindu - Ni Made Sri Windati; I Ketut Sudarsana (Kamaya: Jurnal Ilmu Agama, 2020)
This study aims to determine the inclusion of Hindu religious inclusive attitudes in SMA Dwijendra Denpasar. Practices of violence in the name of religion, and fundamentalists, radicalism, until terrorism, lately increasingly prevalent in the country. Therefore inclusive diversity must be developed in Indonesia. In order to create a harmonious, peaceful, safe, peaceful and prosperous society, it is necessary to build an inclusive attitude towards diversity. Schools are the right means to teach religion, so it is very suitable if religious education is included in the curriculum of learning in schools. One effort that can be carried out by SMA Dwijendra Denpasar to create harmony between students of different religions is to instill an inclusive attitude of Hinduism in class XI students who are Hindu through learning Hindu religious education to transform religious knowledge and values ​​of religious teachings, so as to be able to create harmonious school atmosphere.